Clinical and theoretical relevance of responses to analogues of psychotic experiences in people with psychotic experiences with and without a need-for-care: an experimental study. Issue 5 (4th April 2020) - Ward, Thomas; Garety, Philippa. A; Jackson, Mike; Peters, Emmanuelle
Abstract: Background: Certain ways of responding to psychotic experiences (PEs) appear more commonly associated with clinical distress (e.g. avoidance) and other ways with benign or positive outcomes (e.g. reappraisal and acceptance). Past research has largely been limited to retrospective self-report. We aimed to compare clinical and non-clinical individuals on experimental analogues of anomalous experiences. Method: Response styles of two groups with persistent PEs (clinical n = 84; non-clinical n = 92) and a control group without PEs ( n = 83) were compared following experimental analogues of thought interference (Cards Task, Telepath) and hearing voices (Virtual Acoustic Space Paradigm). Results: The non-clinical group with PEs were less likely to endorse unhelpful response styles, such as passive responding or attempts to avoid, suppress, worry about or control mental experiences, compared with the clinical group on all three tasks. The clinical group were more likely to endorse unhelpful response styles compared with controls on two out of three tasks (Cards Task and Telepath). The non-clinical group performed similarly to controls on unhelpful responding across all tasks. There were no group differences for helpful response styles, such as cognitive reappraisal or mindful acceptance of experiences. Conclusions: In line with cognitive models of psychosis, the findings suggest that the way in which individuals respond to unusual experiences may be an important factor in understanding clinical distress, supporting the therapeutic rationale of targeting potentially unhelpful patterns of response.